초보자의 경쟁상태불안과 주의초점이 골프 퍼팅 수행력에 미치는 영향 - 김영준; Youngjoon Kim; 모단단; Dandan Mao; 신석환; Seakhwan Shin; 권택용; Myoungjin Shin; 신명진; Taegyong Kwon (Ch'eyuk kwahak yŏn'gu, 2024)
[목적] 본 연구는 주의초점이 초보자의 경쟁상태불안과 운동수행에 미치는 영향을 확인하는 것을 목적으로 하였다. [방법] 골프 퍼팅 경험이 전혀 없는 48명의 대학생을 피험자로 선정하였으며 내적-주의초점, 외적-주의초점, 전체적-주의 초점, 통제 집단에 각각 12명씩 무선으로 배정하였다. 모든 피험자들은 습득단계, 비경쟁 상황, 경쟁 상황에서 5m 거리의 골프 퍼팅을 실시하였다. [결과] 내적-주의초점, 전체적-주의초점, 통제 집단은 경쟁 상황에서 비경쟁 상황과 유사한 수준의 골프 퍼팅 정확성과 일관성을 나타낸 반면, 외적-주의초점 집단의 골프 퍼팅 정확성과 일관성은 경쟁 상황에서 비경쟁 상황보다 유의하게 저하된 수준으로 나타났다. 또한 전체적-주의초점 집단은 경쟁 상황과 비경쟁 상황 모두에서 통제 집단보다 유의하게 높은 수준의 골프 퍼팅 정확성을 보였다. [결론] 전체적-주의초점은 초보자가 운동기술을 효과적으로 학습하고, 학습한 운동기술을 경쟁상태불안이 증가한 상황에서 효과적으로 재현하기 위한 전략으로서 활용될 수 있다. 반면, 외적-주의초점은 경쟁상태불안이 증가한 상황에서 초보자의 효과적인 운동수행을 유도하기 위한 전략으로서 고려될 수 없다. PURPOSE This study examined the effects of focus of attention on beginning golfers’ competitive anxiety and motor performance. METHODS Forty-eight college students with no prior golf putting experience were selected as participants and randomly assigned to internal-focus, external-focus, holistic-focus, and control groups (12 participants each). All subjects performed 5-m golf putting in acquisition, noncompetitive, and competitive situations. RESULTS In competitive situations, the internal-focus, holistic-focus, and control groups showed golf putting accuracy and consistency similar to those in noncompetitive situations, whereas the external-focus group’s golf putting accuracy and consistency were significantly lower in competitive situations than in noncompetitive situations. In addition, the holistic-focus group showed significantly higher golf putting accuracy than the control group in both competitive and noncompetitive situations. CONCLUSIONS Holistic-focus can be used effectively as a strategy for beginners to learn motor skills and reproduce learned motor skills when state anxiety increases. However, external attention focus cannot be considered a strategy to induce effective beginners’ exercise performance when competitive state anxiety increases.